PENGARUH MODEL PEMBELAJARAN BERBASIS LINGKUNGAN TERHADAP HASIL BELAJAR IPAS KELAS IV SD NEGERI 124385 P.SIANTAR T.A 2024/2025 - Ramson Butar Butar; Osco Sijabat; Hetdy Sitio (JOURNAL SAINS STUDENT RESEARCH, 2024)
The aim of this research is to determine the effect of the environment-based learning model on the science and science learning outcomes of class IV students at state elementary school 124385 p.siantar T.A 2024/2025. This type of research is quantitative research using experimental methods. The type of research used is pre-experimental using a One Group Design Pretest-Posttest design. Hypothesis test results with a significance level of = 0.05 and an rtable of 1.426, tcount of 13.716. Thus tcount > rtable 13.716 > 1.426P), it can be concluded that there is an influence of the environment-based learning model on the science and science learning outcomes of fourth grade students at state elementary schools 124385 P.Siantar T.A 2024/2025